Eco-Theology from a Christian Perspective (A Study of Verses on Environmental Conservation) - Suryani Suryani; Nur Fitriyana; Nugroho Nugroho (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This article discusses ecotheology in the perspective of Christianity by examining Genesis 1:26–28 and Psalm 24 as biblical foundations for human responsibility toward the environment. The purpose of this study is to explore the theological understanding of the cultural mandate and divine ownership in relation to the preservation of creation. The research employed a library study method with a qualitative-descriptive approach, analyzing biblical texts, theological literature, and previous studies. The findings show that humans are called to be stewards of creation, not arbitrary rulers, so that the management of nature must be carried out with full accountability to God. The integration of Genesis 1:26–28 and Psalm 24 provides a theological framework that emphasizes the balance between authority and ecological responsibility. Thus, Christian ecotheology is not merely conceptual but also a practical calling for the church and believers to make environmental preservation an integral part of faith and worship to God.